PROGNOSTIC SIGNIFICANCE OF TP53 GENE MUTATIONS WITH ACUTE LEUKOSIS (Spectrum Journal of Innovation, Reforms and Development, 2022)
Acute leukemia is a malignant tumor of the hematopoietic system. It has a poor prognosis due to a number of complex features1. Based on the rate of development and cytogenetic analysis, leukemia has been classified into four main types 2: acute lymphocytic leukemia (ALL), acute myeloid leukemia (AML). Although research on leukemogenesis has been carried out for many years. The mechanisms underlying the development of this hematologic malignancy remain unclear. Multiple risk factors considered implicated in leukemia, and genetic factors such as constitutional genetic variation in components of DNA damage response pathways have become the subject of research. The TP53 protein functions by regulating cell cycle arrest, DNA repair, apoptosis and gene transcription to provide cellular responses to DNA damage. Frequent mutations and differential expression of TP53 in various types of cancer highlight the important role of p53. in carcinogenesis and tumor progression. Functional single nucleotide polymorphism (SNP) at codon 72 It was shown that the TP53 gene (rs1042522), encoding the transversion of G to C (Arg to Pro), is associated with interindividual differences in TP53 expression in malignant tumors, including leukemia. In addition, he has it was reported that the Arg72 variant induces apoptosis markedly better than the Pro72 variant. In addition, he has it was reported that the Arg72 variant induces apoptosis markedly better than the Pro72 variant. Thus, this genetic polymorphism holds promise as a potential biomarker for leukemia. To date, numerous studies have investigated the relationship between the Arg72Pro TP53 polymorphism and susceptibility to leukemia, but the effect of the Arg72Pro TP53 polymorphism on leukemia was still controversial.